2022
DOI: 10.1186/s12871-021-01559-4
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic assessment of preoperative gastric volume in patients with dyspepsia: a prospective observational study

Abstract: Background Patients undergoing gastroenteroscopy during sedation are prone to aspiration, and most patients with dyspepsia have delayed gastric emptying. This study aimed to investigate the feasibility of measuring the gastric antrum cross-sectional area (CSA) to supply a novel clinical diagnostic reference value in patients with dyspepsia. Methods Patients with dyspepsia undergoing elective gastroscopy were included. The Perlas qualitative 0–2 gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Severe injury usually occurs as tenderness and hematoma in the angular ligament of the medial malleolus, while injury occurs as a dull pain in the medial sulcus of the joint. Anterior symptoms [ 26 ]. There is a noticeable sensitivity in the front and bottom of the medial malleolus tip, subcutaneous ecchymosis can be seen, and there is depression or nothing on the inside of the ankle.…”
Section: Results and Analysismentioning
confidence: 99%
“…Severe injury usually occurs as tenderness and hematoma in the angular ligament of the medial malleolus, while injury occurs as a dull pain in the medial sulcus of the joint. Anterior symptoms [ 26 ]. There is a noticeable sensitivity in the front and bottom of the medial malleolus tip, subcutaneous ecchymosis can be seen, and there is depression or nothing on the inside of the ankle.…”
Section: Results and Analysismentioning
confidence: 99%
“…In recent studies, the effectiveness of imaging complete cross-sections via ultrasonography has been shown to be reduced when the stomach is filled with solid food [ 11 ]. While high correlation coefficients have been noted in various mathematical models to predict gastric volumes, with adjusted R 2 values ranging from 0.60 to 0.73, these models have been found to be less reliable in cases of organic dyspepsia and gastroparesis [ 49 ]. This has spurred the development of computational simulations and modeling of gastric flow, offering valuable insights through integrative and quantitative in silico studies that may be challenging to perform experimentally [ 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cut-off value for patients with organic dyspepsia to predict gastric volume >0.8 ml/kg was 10.0 cm 2 , with a sensitivity of 92. 7% and a specificity of 82.4% [10]. However, it does not access gastrointestinal dynamics.…”
Section: Gastric Ultrasoundmentioning
confidence: 99%
“…The pretest probability of 50% a sensitivity of 100% and a specificity of 97.5% with a positive predictive value of 97.6% and a negative predictive value of 100%. Tan et al [10] with 117 patients, reported for a gastric volume of >0.8 ml/kg, cut-off values for functional dyspepsia and organic dyspepsia were 6.7 cm 2 and 10.0 cm 2 , respectively. The cut-off value for patients with FD to predict gastric volume of >0.8 ml/kg was 6.7 cm 2 , with a sensitivity of 100% and a specificity of 48.7%.…”
Section: Gastric Ultrasoundmentioning
confidence: 99%